Probabilistic Manner Based on the Basic Functional Practical and Probabilistic Parameters - ديوب, محمد صقر (Latakia University Journal -Engineering Sciences Series, 2020)
Through practical experience to study heavy machinery it becomes clear that the most expressive indicators of the investment stress status are the operational and specific indicators in probabilistic parameters. The probable characteristic of the stresses in machines is determined as a sum of probability factors (predictive). In this study, probable indicators of dynamic stresses in machines are determined based on the probable characteristic of the mutual influence of the binary (human- machine) at a probable (predictive) moment which expresses the period or the moment the multiple components of the machine or the system as a whole start entering in motion or the moment you start moving and driving the machine. The formation of disturbance and the vibrations in the mechanism and the components of the machine is determined through the conclusion of a potential mathematical law that includes many potential elements during work and loading. This research focuses on finding a probabilistic mathematical law that includes many potential elements during work and loading in order to anticipate and predict the occurrence of disturbances and vibrations in mechanisms and heavy machinery components in order to find ways to exclude these disturbances and vibrations or delay their occurrence which prolong the default life span of the elements and the machine as a whole.